PENGARUH GAYA KEPEMIMPINAN DAN MOTIVASI KERJA TERHADAP TINGKAT TURNOVER PEGAWAI - ENCEP SAEFULLAH; LISTIAWATI; KIKI ZAKIYAH RIMANDANI (Pusat Publikasi dan Penerbitan Karya Ilmiah STIE Indonesia Malang, 2018)
This study intention to determine the effect of leadership style and work motivation on employeeturnover rate in the clinic and pharmacy Buchori Serang. Style of leadership and motivationthat support is needed for organizations or companies to reduce the employee turnover rate. Thisresearch is descriptive and associative by using a quantitative approach. The subjects were allemployees of the pharmacy and clinic Buchori Serang Banten. Collecting data usingquestionnaires and scales used is a Likert scale. While the analysis of data using linearregression and correlation analysis. Based on the results of hypothesis testing leadership style(H1) proves that the leadership style partial effect on the level of employee turnover. This isevidenced by thitung 2.751> 2.023 ttabel while Hypothesis testing results of work motivation (H2)proved that motivation is not partial effect on the level of employee turnover. This is evidencedby thitung 1.007 < ttabel 2023.The results of statistical calculations show value of fhitung = 4.761 with significant value 0.014,significance value less than 0.05. And fhitung 4.761 greater than ftable 3.23. This means that thestyle of leadership and motivation to work simultaneously affect the turnover rate of employeesat the Clinic and Pharmacy Buchori Serang. The amount of the percentage influence leadershipstyle and work motivation on employee turnover rate in the clinic and pharmacy BuchoriAttack of 0.196 or 19.6% using coefficients of determination that is determined by the value ofR Square rest influenced by other variables that are not described in this study.